A DNA binding domain is contained in the C-terminus of wild type p53 protein. - Foord, O S (1991)
In the present study we evaluated the DNA binding activity of wild type and mutant p53 proteins that were isolated from bacterial expression vectors. A comparison of the binding activities of the various purified p53 proteins, assessed by their ability to bind DNA cellulose columns, indicated that wild type p53 has a higher affinity to DNA than have mutant p53 forms. Furthermore, only wild type p53 was able to bind genomic DNA upon electrophoretic protein blotting. As specific deletion of the C-terminal region of wild type p53 totally abolished binding to genomic DNA, it was concluded that the 47 C-terminal amino acids contain the DNA binding region. The fact that the N-terminus contains a transcription activation region whereas the C-terminus contains a DNA binding domain places p53 in the family of typical transcription factors. Our experiments show that the topographical positioning of these domains plays an important role in the activity of wild type p53.